Interferons in Pain and Infections: Emerging Roles in Neuro-Immune and Neuro-Glial Interactions - Tan, Ping-Heng; Ji, Jasmine; Yeh, Chun-Chang; Ji, Ru-Rong (Frontiers in Immunology, 2021)
Abstract Interferons (IFNs) are cytokines that possess antiviral, antiproliferative, and immunomodulatory actions. IFN-α and IFN-β are two major family members of type-I IFNs and are used to treat diseases, including hepatitis and multiple sclerosis. Emerging evidence suggests that type-I IFN receptors (IFNARs) are also expressed by microglia, astrocytes, and neurons in the central and peripheral nervous systems. Apart from canonical transcriptional regulations, IFN-α and IFN-β can rapidly suppress neuronal activity and synaptic transmission via non-genomic regulation, leading to potent analgesia. IFN-γ is the only member of the type-II IFN family and induces central sensitization and microglia activation in persistent pain. We discuss how type-I and type-II IFNs regulate pain and infection via neuro-immune modulations, with special focus on neuroinflammation and neuro-glial interactions. We also highlight distinct roles of type-I IFNs in the peripheral and central nervous system. Insights into IFN signaling in nociceptors and their distinct actions in physiological vs. pathological and acute vs. chronic conditions will improve our treatments of pain after surgeries, traumas, and infections.